Twilight in the leadership playground: subrealism and the training of the business self. Issue 3 (4th May 2017) - Lezaun, Javier; Muniesa, Fabian
ABSTRACT: What sort of reality is produced and conveyed to the business trainee through the set of pedagogical techniques that characterize the experiential business curriculum, and how does immersion in this particular kind of reality configure the business self? This essay discusses some of the rhetorical and theatrical contrivances that are used to generate artificial business situations in which the student can experience a moment of decision and test his quality as a leader. These training formulas, we argue, rely on the therapeutic hope of dramaturgical self-realization, but often degenerate into a form of regressive fetishism in which the fantasy of existential resolve and serious decision-making can be playfully and safely enacted. Surrealism and its demise provide an angle from which the peculiar fragility of these operations can be understood: what the experiential business curriculum provides, in this interpretation, amounts to a sort of subrealist shield, a protective dilution of the challenges that await in the world at large. When the element of the ethical pledge is added to this compendium of techniques, the result is a self-referential (and essentially indulgent) form of spiritual exercise solely oriented to the auto-elevation of the business self.